2009
DOI: 10.1097/coc.0b013e31817be58e
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of ERCC1, Thymidylate Synthase, and Glutathione S-Transferase π for 5-FU/Oxaliplatin Chemotherapy in Advanced Colorectal Cancer

Abstract: Immunohistochemical study of ERCC1 and TS may be useful for the prediction of clinical outcome in patients with advanced colorectal cancer treated with 5-FU and oxaliplatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 27 publications
4
55
1
1
Order By: Relevance
“…To determine whether knockdown of PDK4 sensitizes colon cancer cells to other chemotherapeutic drugs, HCT116 cells were treated with oxaliplatin, an alkylating agent commonly used in combination with 5-FU for treating advanced colon cancer (30,31). Similar to 5-FU, oxaliplatin treatment induced more apoptosis in PDK4 knockdown cells than in control cells, as shown by DNA fragmentation assays and PARP cleavage (Fig.…”
Section: Genetic or Pharmacological Inhibition Of Pdk4 Sensitizes Colmentioning
confidence: 99%
“…To determine whether knockdown of PDK4 sensitizes colon cancer cells to other chemotherapeutic drugs, HCT116 cells were treated with oxaliplatin, an alkylating agent commonly used in combination with 5-FU for treating advanced colon cancer (30,31). Similar to 5-FU, oxaliplatin treatment induced more apoptosis in PDK4 knockdown cells than in control cells, as shown by DNA fragmentation assays and PARP cleavage (Fig.…”
Section: Genetic or Pharmacological Inhibition Of Pdk4 Sensitizes Colmentioning
confidence: 99%
“…Later studies confirmed the predictive role of ERCC1 in NSCLC [12,37] and other types of cancer, such as colorectal cancer [17], gastric carcinoma [16,[38][39], and esophageal cancer [40]. Our study showed that patients with lower expression of ERCC1 had relatively higher DCR than patients with higher gene expression when they received platinum-based chemotherapy, which is consistent with previous studies.…”
Section: Discussionsupporting
confidence: 82%
“…The similar mete-analysis was performed by Chen and the same conclusion was gained (Chen et al, 2010). In addition, many papers evaluated the relation between ERCC1 status and response to chemotherapy have been reported in various human cancers including Colorectal Cancer, bladder cancer, cervical cancer, Head and Neck Cancer, and most of studies showed ERCC1 expression was a predictor of response to chemotherapy (Handra-Luca et al, 2007;Braun et al, 2008;Kim et al, 2009;Ishibashi et al, 2010;Kim et al, 2010;Hayes et al, 2011;Kawashima et al, 2011;Park et al, 2011;Sun et al, 2012). In 2008, Lin et al performed a cohort study to evaluate the difference of ERCC1 protein expression levels between 36 sensitive cases and 27 resistant cases of serous ovarian cancer receiving neoadjuvant chemotherapy and demonstrated that ERCC1 protein expression levels in resistance group of serous ovarian cancer were significantly higher than those of sensitivity group, and Lin et al's study was in accordance with our meta-analysis (Lin et al, 2008).…”
Section: Discussionmentioning
confidence: 61%